EFFECT OF GREEN MANAGEMENT ON SUSTAINABILITY OF GLOBAL FAST FOOD RESTAURANTS: ANALYSIS OF NIGERIA PERSPECTIVE - Olawale, Yinusa Alabi (2025)
This study investigated the effect of green management on sustainability of global fast food restaurants in Ilorin metropolis, Kwara state, Nigeria. Specifically, the objective of the study examined; the effect of green products on product innovation of global fast food restaurants; the impact of green marketing on competitive advantage of global fast food restaurants. A survey method with census was adopted to examine 58 staff of fast food restaurants administered questionnaire. Collected data was analyzed using multiple regression analysis to test the hypotheses. The findings of the study revealed that green product is significant to product innovation of fast-food outlets with R 2 value of 97.0%; and green marketing has significant effect on the competitive advantage with R 2 value of 94.5%. The study concluded that green management has positive effect on organizational sustainability. It therefore recommended among others that Fast-food outlets should ensure that they focus on green production in managing their production and operation department. Also, the management of Fast-food outlets should ensure that it makes use of green marketing strategies that can help it achieve higher competitive advantage in the industry.